The experimental evaluation of the statistical characteristics of the compressor front support vibration of the gas compressor units - Лідія Ігорівна Фешанич (Tehnologìčnij Audit ta Rezervi Virobnictva, 2014)
The use of statistical methods for the analysis of parameters is discussed in this article and an example of the results in our research is given. The main aim is to analyze the statistical characteristics of the signal, based on experimental data obtained at gas compressor unit №9 of booster compressor station of underground gas storage "Bilche-Volytsya." An example of research of one informative parameter characterizing the operating mode of the compressor – the vibration displacement of front support compressor is given in the article. It is determined such signal characteristics as expectance, dispersion, histogram, empirical and theoretical density, distribution law, empirical and theoretical distribution function and other. This made it possible to prove the feasibility of lognormal distribution law using for this parameter and use it to solve problems of surge and anti-surge regulation protection.